2021
DOI: 10.1371/journal.pone.0259223
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of gender as a social determinant of health in epidemiology—A scoping review

Abstract: Background The relevance of gender as a social determinant of health and its role in the production of health inequalities is now broadly acknowledged. However, the plethora of existing approaches to capture gender, which often stem from disciplines outside of epidemiology, makes it difficult to assess their practicality and relevance for a given research purpose. We conducted a scoping review to 1) map the evidence of how gender can be operationalised in quantitative epidemiology and 2) design a tool to criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 80 publications
1
36
0
1
Order By: Relevance
“…In line with a recently published scoping review by Miani and colleagues [ 30 ], we found that the majority of instruments are based on a binary distinction between femininity and masculinity, although, in many cases, they are not considered mutually exclusive. We identified several instruments that measure the participants’ degree of belonging to a sex and/or gender category or their conformity with stereotypical gender roles.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In line with a recently published scoping review by Miani and colleagues [ 30 ], we found that the majority of instruments are based on a binary distinction between femininity and masculinity, although, in many cases, they are not considered mutually exclusive. We identified several instruments that measure the participants’ degree of belonging to a sex and/or gender category or their conformity with stereotypical gender roles.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, we conducted a thorough and comprehensive search following the PRISMA Extension for Scoping Reviews, which allowed a broad range of approaches to measuring sex and/or gender to be included within our scoping review. This distinguishes our review from previous reviews that focused on gender only [ 30 , 31 ]. Thus, our scoping review clearly demonstrates that further elaboration or new development of instruments to operationalise sex and gender comprehensively are needed to be able to assess the impact of sex/gender dimensions on health and to fulfil the requirements of expert associations, funding agencies, and scientific journals to consider sex and gender in research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While in everyday language, sex and gender are often used interchangeably, distinctions between the terms are now recognised within legal and academic circles. Broadly, sex refers to biological characteristics, while gender refers to a sociocultural construct 3 . Biological sex is often assigned at birth based on anatomical characteristics; however, it can also be defined by chromosomal sex, with phenotypical variation influenced by hormones.…”
mentioning
confidence: 99%
“…Broadly, sex refers to biological characteristics, while gender refers to a sociocultural construct. 3 Biological sex is often assigned at birth based on anatomical characteristics; however, it can also be defined by chromosomal sex, with phenotypical variation influenced by hormones. Although biological sex is often thought of as a male and female binary, intersex and hormonal variations occur in individuals, such that sex may similarly be considered across a spectrum.…”
mentioning
confidence: 99%